The human genes for complement components 6 (C6) and 9 (C9) are closely linked on chromosome 5. - Rogne, S (1991)
We have used a cDNA probe for human complement component 9 (C9), which detects three DNA polymorphisms, to analyse the inheritance of C9 in families informative for C6 protein variants. We found that these genes are closely linked with a lod score of 9.28 at recombination fraction 0.00. There is not indication of allelic association.